Benchmarking of Philippine GDP and its components a comparison of selected products - Magsombol, Maria Rhoda A. (2006)
This study presents and evaluates different benchmarking techniques that deemed useful in ensuring the continuity of time series data; specifically, th enational accounts of the Philippines. The benchmarking prpcedure takes into account the problem on how to quarterize the available annual estimates to come up with more relevant quarterly series. Four different techniques were considered for this study: the Pro rata method, the Bassie method, the Proportional Denton method, and the Generalized Least Squares method. Upon evaluation of the techniques, the study suggests hat Proportional Denton method performs best in benchmarking the national account series. Meanwhile, since the benchmarking procedures only covers the period 1991-1998, the study also links and eventually rebases the whole national accounts series. The splicing method is found to be the simplest and most applicable technique in linking the current price estimates of GDP while mechanical rebasing method is very helpful in updating the base years for constant price estimation.
"June 2006."
Thesis ( M.Statistics) --University of the Philippines Diliman.
Keywords: Gross domestic product -- Philippines; Benchmarking (Management).